The cost of premature cancer-related mortality: a review and assessment of the evidence. (June 2014) - Hanly, Paul; Pearce, Alison; Sharp, Linda
Abstract : Worldwide, 8.2 million people die of cancer annually. Cancer has a significant societal impact, impinging on countries' economic health. We reviewed methodological aspects, and the main cost results, of studies calculating premature mortality losses from cancer published 2000–2013 and identified gaps in the evidence-base. Thirty-one studies were identified (Europe, 17; USA, 11; Korea, 2; Puerto Rico, (1). The human capital approach dominated (30 studies); studies differed in how they implemented the methodological approach. Aspects of methodology were poorly reported. Premature cancer-related mortality costs are substantial and appear to be rising. The evidence-base has gaps in relation to cancer sites studied and less developed and emerging economies. Comprehensive, standardised, estimates of premature mortality losses are needed if these measures are to be useful in assessing the societal cancer burden.